EFFECTS OF P SIOLOGICAL DOSES OF VIT 4 IN D3 (CHOLECALCIFEROL) ON UCED MOLTING GROWTH IN G T FRES ATER P MACROBRACHIUM ROSENBERGII (de Man) - Metar, S. Y.; Srivastava, P. P.; Jain, K. K.; Manush, S. M.; Raizada, S.; Ayyappan, S. (Journal of Indian Fisheries Association, 2015)
Effects of three different doses of vitamin D3 on molting, growth, andcalcium and phosphate composition of tissue and molt during the grow-outof the giant freshwater prawn Macrobrachium rosenbergii (average weight10.56 t 0.20 g), obtained from a grow-out pond, were studied. Intramusculardoses of vitamin D3 (100, 500 and 2000 IU/kg body weight) were given on the1St, 3rd, 5th, 7th, 9th, 11th, 13th, 15th, 20th, 25 th and 30th days. All the experimentalanimals were fed with a basal diet containing fish meal, shrimp meal, wheatflour, groundnut de-oiled cake, soybean meal and wheat bran at 3% of thebody weight. The numbers of molts were recorded as 20+0.50, 29+1.16, 51+1.87,and 30+1.60 in control, 100, 500 and 2000 IU/kg body weight physiologicaldoses, respectively. Maximum growth was recorded in prawns given 500 IU/kg dose. Survival was between 58.33 Â± 9.13 and 77.77 Â± 8.61%. The ash contentand calcium level increased significantly (p